Enhancing Physicians’ Autonomy through Practical Trainings - Stirparo, Giuseppe; Gambolò, Luca; Bottignole, Dario; Solla, Daniele; Trapani, Martino; Ristagno, Giuseppe; Pregliasco, Fabrizio; Signorelli, Carlo (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. In medical emergencies adherence to standardized clinical protocols is crucial to ensure a better outcome for patients. Newly qualified physicians may play several roles in serving the National Health Service (substituting general practitioners, on-call duty, working in emergency rooms, etc.) in Italy. In these situations, the physician may have to manage critical patients autonomously. Moreover, newly qualified physicians may show a considerable deficiency in routine medical activities. In fact, many universities do not provide a practical simulation training programme, which is why a substantial number of students only face clinical emergencies when they start working after graduation. Study design. A cross-sectional study was performed by engaging medical doctors. Both experienced physicians and newly licensed physicians (graduated less than 24 months ago) were included in the study. Methods. A questionnaire was distributed to each participant during SIMED’s Courses from June 2021 to December 2022. The questionnaire consisted of two sections. The first one analyzed participation in standardized practical courses on medical emergencies (Basic Life Support, Advanced Cardiac Life Support, International Trauma Life Support and a course on Advanced Airway Management). The second section analyzed the perceived autonomy of health professionals in the management of five different work settings, using a 5-point likert scale.Results. 2,168 questionnaires were analyzed, of which 68.7% were from newly qualified doctors and 31.3% from more experienced doctors.The highest rate of physicians who undertook training courses was achieved for the basic life support course (77.5%) and the lowest rate for the advanced trauma course (15.9%). Physicians perceive themselves the highest autonomy in Primary Care setting (63.1%), while in the Emergency Department they perceive themselves with less autonomy (24.0%). In the analyzed sample, experienced physicians show a higher percentage of autonomy than newly qualified doctors (31.4% vs 8.1%) in all scenarios